PENGAMBILAN KEPUTUSAN PENEMPATAN JABATAN STRUKTURAL APARATUR SIPIL NEGARA (ASN): Decision Making Structural Position Placement State Civil Aparature - M Yusuf Barusman; Amelia Citra; Moh Oktavianur; Appin Redaputri (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2020)
Employees are a very important resource for determining the success of a work unit. Efforts to improve the quality of the performance of an ASN is a promotion. The promotion is an award given for work performance and service of ASN, as well as encouragement to further improve work performance and service. One of the main causes is because there is a mismatch between the competencies of employees with the positions they occupy. The discrepancy is caused by the composition of expertise or skills of employees who have not been proportionate. Therefore, it is necessary to have an assessment in determining promotions by taking into account several elements, including formal and informal elements. In both elements there are special criteria as a basis for making an assessment. The method used in this research is Soft System Methodology (SSM) using Analytical Hierarchy Process tools. From the results of the study obtained 2 criteria, namely Formal and Informal. Formal criteria consist of formal education sub rank, rank / goal. space, position training, job experience, years of service, and age, while innovation, creativity, and ideas for developing institutional functions, discipline, ability to collaborate and cooperate with teams, leadership, loyalty, responsibility, ability to communicate well, and political intervention is a sub-criterion of informal criteria. Keywords: decision making, position placement system, state civil aparature, soft system methodology, analytical hierarchy process